Moving Ourselves, Moving Others Motion and Emotion in Intersubjectivity, Consciousness and Language - Foolen, Ad; Lüdtke, Ulrike M.; Racine, Timothy P.; Zlatev, Jordan (Consciousness & Emotion Book Series, 2012)
The close relationship between motion (bodily movement) and emotion (feelings) is not an etymological coincidence. While moving ourselves, we move others; in observing others move - we are moved ourselves. The fundamentally interpersonal nature of mind and language has recently received due attention, but the key role of (e)motion in this context has remained something of a blind spot. The present book rectifies this gap by gathering contributions from leading philosophers, psychologists and linguists working in the area. Framed by an introducing prologue and a summarizing epilogue the volume elaborates a dynamical, active view of emotion, along with an affect-laden view of motion - and explores their significance for consciousness, intersubjectivity, and language. As such, it contributes to the emerging interdisciplinary field of mind science, transcending hitherto dominant computationalist and cognitivist approaches.